Preparation method and application of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) lithium imide-triallyl phosphite organic coating material

By using thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl)imide lithium-tripropylene phosphite organic coating material to coat the high-nickel ternary positive electrode material, the crack problem that occurs during the cycle is solved, and the capacity retention and rate performance is significantly improved, and it is suitable for high-temperature/high-pressure environments.

CN119581511AActive Publication Date: 2025-03-07HARBIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411582750.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-07
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

High-nickel ternary cathode materials are prone to intergranular and intragranular cracks during the circulation process, resulting in capacity attenuation and increased side reactions, hindering their large-scale commercial application.

Method used

The organic coating material of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl)imide lithium-tripropylene phosphite is used to form a uniform coating layer on the surface of the positive electrode material through wet coating technology to reduce the side reaction between the positive electrode material and the electrolyte solution.

Benefits of technology

It effectively suppresses the capacity diving phenomenon of SC-NCM811, improves circulation performance and rate performance, and performs excellently in high temperature/high pressure conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581511A_ABST
    Figure CN119581511A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of an organic coating material, in particular to a preparation method and application of a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) lithium imide-triallyl phosphite organic coating material. In order to solve the problem of high reactivity of SC-NCM, a novel organic coating material, namely thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) lithium imide-triallyl phosphate (SH-LiCPSI-TLP), is provided by combining the influence of the type of the coating material and the form of a coating layer on the performance of the positive electrode material; as the Young modulus of an organic material is generally lower than that of an inorganic material, a uniform coating layer can be formed on the surface of the positive electrode material by adopting a simple wet coating method. An electrochemical test shows that after SH-LiCPSI-TLP is coated, the capacity diving phenomenon of the SC-NCM811 can be effectively inhibited, and under the 1C multiplying power, the capacity retention ratio is still 52.78% even if the SH-LiCPSI-TLP is circulated for 600 circles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of an organic coating material. Background Art

[0002] High nickel ternary cathode material Ni-rich NCM (Ni-rich LiNi x Co y Mn 1-x-y O2, x>0.6) is regarded as an ideal cathode for high energy density lithium-ion batteries due to its high specific capacity and good rate performance. However, as the nickel content increases, high nickel ternary cathode materials face the problems of microcracks and aggravated side reactions while gaining specific capacity. These problems have become the key factors hindering the large-scale commercial application of high nickel ternary cathode materials.

[0003] During the cycle of polycrystalline high-nickel ternary materials (PC-NCM), the anisotropic stress accumulation between primary particles leads to intergranular cracks in secondary particles, which is the main reason for the rapid decay of its capacity. The single-crystal high-nickel ternary positive electrode material (SC-NCM) is composed only of primary particles. Compared with PC-NCM, it can fundamentally solve the problem of intergranular cracks caused by stress accumulation between grains during the cycle. Compared with intergranular cracks, intragranular cracks are smaller in size, so their impact on high-nickel ternary positive electrode materials is significantly reduced. However, the impact of intragranular cracks cannot be ignored.

[0004] The generation of intracrystalline cracks mainly comes from two aspects: first, the high temperature during the production process causes defects such as dislocations to appear inside the Ni-rich NCM structure. As the cycle progresses, these defects become the starting point of intracrystalline cracks; second, the interface side reaction causes an irreversible phase change on the crystal surface, accompanied by the accumulation of stress, which eventually leads to the generation of intracrystalline cracks. At present, the synthesis process of SC-NCM relies on a high-temperature synthesis environment, so reducing the degree of interface side reactions has become an effective measure to reduce intracrystalline cracks. In addition, Ni in Ni-rich NCM 4+ The content is high, due to Ni 4+ Due to the high reactivity of Ni-rich NCM, the degree of side reaction between Ni-rich NCM and electrolyte also increases significantly. Therefore, for SC-NCM, reducing the degree of side reaction between the positive electrode material and the electrolyte can effectively reduce the generation of intergranular cracks and the impact of side reactions on the positive electrode material, which is also the premise for SC-NCM to eventually move towards industrialization.

[0005] Surface coating is a modification strategy that can effectively hinder the reaction between the positive electrode material and the electrolyte. The principle is to build a protective layer between the positive electrode material and the electrolyte to prevent direct contact between the positive electrode material and the electrolyte. For Ni-rich NCM, surface coating can effectively reduce the negative effects of high reactivity and significantly improve its interfacial stability and electrochemical stability. Therefore, the research on surface coating modification of Ni-rich NCM has received much attention from scientific researchers and some related companies.

[0006] The type of coating material affects its effect on the positive electrode material. Coating materials with a stable chemical state can protect the positive electrode for a long time; lithium-containing compounds (organic / inorganic) can usually improve the rate performance of the positive electrode material. In addition, the morphology of the coating material on the surface of the positive electrode also has a certain influence on its performance. Generally, a coating layer with uniform coating and moderate thickness is considered to be an ideal coating layer morphology. However, in the coating process of existing inorganic materials, high temperature is required to provide thermodynamic power, but high temperature has an impact on the structural stability of the positive electrode material; in addition, when the coating material with slow lithium ion kinetics is coated on the surface of SC-NCM811, it will affect the rate performance of SC-NCM811, and the coating state of the coating layer also affects the performance of the positive electrode material after the overall coating. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a preparation method and application of a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material.

[0008] The organic coating material prepared by the present invention can reduce the complexity of the coating process, reduce the cost, and ensure the uniformity of the coating layer and the possibility of large-scale production. The combination with lithium salt can effectively increase the lithium ion dynamics of the organic coating material, thereby providing protection for the positive electrode material and increasing its rate performance.

[0009] Since the structure of phosphite is relatively stable, choosing it as the coating material can increase the thermal stability and high-voltage resistance of the electrode material after coating.

[0010] A method for preparing a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material is specifically completed by the following steps:

[0011] 1. Preparation of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium:

[0012] ①, at room temperature, sodium hydrosulfide and lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide are added to anhydrous methanol, and then heated under reflux for a period of time under nitrogen protection. After the reaction is completed, impurities are removed by filtration, and the filtrate is rotary evaporated to obtain reaction product I;

[0013] ②, add acetonitrile to the reaction product I, stir evenly and filter again, and perform rotary evaporation on the filtrate to obtain the reaction product II; dry the reaction product II in an oven to obtain thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium;

[0014] 2. Preparation of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite:

[0015] ①, at room temperature, add thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium, tripropylene phosphite and azobisisobutyronitrile to anhydrous tetrahydrofuran, and then heat under reflux for a period of time under nitrogen protection. After the reaction is completed, the filtrate is rotary evaporated to obtain reaction product III;

[0016] ②. Add the reaction product III into dichloromethane, stir evenly and filter again, and perform rotary evaporation on the filtrate to obtain the reaction product IV; dry the reaction product IV in an oven to obtain the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material.

[0017] A thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material is used for coating anode materials of lithium ion batteries.

[0018] Principles and advantages of the present invention:

[0019] The present invention aims to solve the problem of high reactivity of SC-NCM. Combining the influence of coating material type and coating layer morphology on the performance of positive electrode materials, a new organic coating material is proposed: thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite (SH-LiCPSI-TLP). Since the Young's modulus of organic materials is generally lower than that of inorganic materials, a uniform coating layer can be formed on the surface of the positive electrode material by a simple wet coating method. Electrochemical tests show that after SH-LiCPSI-TLP coating, it is effective to inhibit the SC-NCM8 11 Capacity diving phenomenon: at 1C rate, even after 600 cycles, the capacity retention rate is still 52.78%, while the capacity retention rate of the uncoated SC-NCM811 is only 19.74% after 600 cycles; under high temperature / high pressure conditions, the cycle performance is still better than that of the uncoated SC-NCM811; in addition, due to the presence of lithium salt in SH-LiCPSI-TLP, the coated SC-NCM811 exhibits a higher discharge capacity and excellent rate performance: at 5C rate, the coated SC-NCM811 still has 107.18 mAh g -1 The discharge specific capacity of SC-NCM811 is significantly improved at a 3C rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is the structural formula and H NMR spectrum of the substance. Figure 1 a is the synthesis reaction equation of SH-LiCPSI-TLP, b is the H-NMR spectra of LiCPSI and SH-LiCPSI, and c is the H-NMR spectra of TLP and SH-LiCPSI-TLP;

[0021] Figure 2 XRD comparison diagram of SC-NCM811 powder before and after coating;

[0022] Figure 3 Figure a is a scanning electron microscope image of PristineSC-NCM811, and figure b is a scanning electron microscope image of M-TLP@SC-NCM811;

[0023] Figure 4 The scanning electron microscope image and EDS mapping image of M-TLP@SC-NCM811, in which a is the scanning electron microscope image, b is Ni, c is Co, d is P, e is S, f is F, and g is N;

[0024] Figure 5 Cyclic voltammetry curves from the first to the fifth cycle of Pristine SC-NCM811 and M-TLP@SC-NCM811, where a is Pristine SC-NCM811 and b is M-TLP@SC-NCM811;

[0025] Figure 6 This is a comparison of the cycle performance of M-TLP@SC-NCM811||Li and Pristine SC-NCM811||Li. In the figure, a is the standard voltage cycle performance at room temperature, b is the standard voltage cycle performance at high temperature, and c is the high voltage cycle performance at room temperature;

[0026] Figure 7 This is a comparison of the rate performance and lithium ion diffusion rate of M-TLP@SC-NCM811||Li and Pristine SC-NCM811||Li. In the figure, a is the discharge capacity of M-TLP@SC-NCM811||Li and Pristine SC-NCM811||Li at different rates, and b is the 3C-5C high-rate cycle performance of M-TLP@SC-NCM811||Li and Pristine SC-NCM811||Li. DETAILED DESCRIPTION

[0027] Specific implementation method 1: This implementation method is a method for preparing a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material, which is specifically completed according to the following steps:

[0028] 1. Preparation of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium:

[0029] ①, at room temperature, sodium hydrosulfide and lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide are added to anhydrous methanol, and then heated under reflux for a period of time under nitrogen protection. After the reaction is completed, impurities are removed by filtration, and the filtrate is rotary evaporated to obtain reaction product I;

[0030] ②, add acetonitrile to the reaction product I, stir evenly and filter again, and perform rotary evaporation on the filtrate to obtain the reaction product II; dry the reaction product II in an oven to obtain thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium;

[0031] 2. Preparation of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite:

[0032] ①, at room temperature, add thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium, tripropylene phosphite and azobisisobutyronitrile to anhydrous tetrahydrofuran, and then heat under reflux for a period of time under nitrogen protection. After the reaction is completed, the filtrate is rotary evaporated to obtain reaction product III;

[0033] ②. Add the reaction product III into dichloromethane, stir evenly and filter again, and perform rotary evaporation on the filtrate to obtain the reaction product IV; dry the reaction product IV in an oven to obtain the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material.

[0034] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the preparation method of lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide described in step 1① is specifically completed according to the following steps: 200mmolLiOH·H2O is dissolved in 20mL C2H3N solution, and then 100mmol C3H6Cl2O2S and 100mmolCH2F3NO2S are added in turn in an ice-water bath, stirred for 48h, and then filtered, and the filtrate is concentrated at 50°C with a rotary evaporator to obtain a reaction product; the reaction product is dissolved in 20mL dichloromethane, filtered again, and the filtrate is dried at 50°C with a rotary evaporator to obtain lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide. The other steps are the same as those in specific embodiment 1.

[0035] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the molar ratio of sodium hydrosulfide to lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide described in step 1 ① is 2:1; the volume ratio of the amount of sodium hydrosulfide described in step 1 ① to anhydrous methanol is (15mmol-25mmol): (15mL-30mL); the heating reflux temperature described in step 1 ① is 65°C, and the heating reflux time is 20h-28h; the rotary evaporation temperature described in step 1 ① is 50°C-55°C. The other steps are the same as those in specific embodiment 1 or 2.

[0036] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the volume ratio of the reaction product I and acetonitrile described in step 1 ② is 1 mL: (20 mL to 60 mL); the temperature of the rotary evaporation described in step 1 ② is 50° C. to 55° C.; the temperature of the drying described in step 1 ② is 70° C. to 90° C., and the drying time is 10 h to 14 h. The other steps are the same as those of specific embodiments 1 to 3.

[0037] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the molar ratio of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium, tripropylene phosphite and azobisisobutyronitrile described in step 2① is (3mmol~4mmol):(0.5mmol~1.5mmol):(2.5mmol~3.5mmol); the volume ratio of the amount of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium described in step 2① to anhydrous tetrahydrofuran is (3mmol~4mmol):(15mL~30mL); the heating reflux temperature described in step 2① is 65℃, and the heating reflux time is 10h~14h; the rotary evaporation temperature described in step 2① is 50℃~55℃. The other steps are the same as those of specific embodiments 1 to 4.

[0038] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the temperature of the rotary evaporation in step 2 ② is 50°C; the temperature of the drying in step 2 ② is 70°C to 90°C, and the drying time is 10h to 14h. The other steps are the same as those in specific embodiments 1 to 5.

[0039] Specific implementation method seven: This implementation method is a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material used for coating anode materials of lithium-ion batteries.

[0040] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material is used to coat the positive electrode material of a lithium ion battery, which is specifically completed in the following steps:

[0041] 1. Thoroughly stir the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material and N-methylpyrrolidone in a glove box to obtain a SH-LiCPSI-TLP / NMP mixed solution;

[0042] The mass fraction of the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material in the SH-LiCPSI-TLP / NMP mixed solution described in step 1 is 15% to 25%;

[0043] 2. Mix the SH-LiCPSI-TLP / NMP mixed solution, SC-NCM811 powder and N-methylpyrrolidone, then heat and stir for a period of time, and when the reaction is finished, completely volatilize the N-methylpyrrolidone to obtain a lithium ion battery positive electrode material coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite. The other steps are the same as those in the first to seventh embodiments.

[0044] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that the mass volume ratio of the SH-LiCPSI-TLP / NMP mixed solution, SC-NCM811 powder and N-methylpyrrolidone described in step 2 is (15mg~25mg):(1g~3g):(5mL~10mL); the temperature of the heating and stirring described in step 2 is 50℃~70℃, and the stirring speed is 350rmin -1 ~500rmin -1 The stirring time is 10 hours to 12 hours. The other steps are the same as those in the first to eighth embodiments.

[0045] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: a method for preparing a positive electrode sheet of a lithium ion battery using a lithium ion battery positive electrode material coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite is specifically completed in the following steps:

[0046] 1. The lithium-ion battery positive electrode material coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite, conductive carbon black and binder were mixed in a mass ratio of 8:1:1, and then N-methylpyrrolidone was added, and stirred at room temperature for 10h to 12h to obtain a positive electrode slurry;

[0047] The mass ratio of the total mass of the lithium-ion battery positive electrode material coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite, conductive carbon black and binder to N-methylpyrrolidone is 1:1; the binder described in step 1 is polyvinylidene fluoride;

[0048] 2. Use an automatic tape casting machine to evenly coat the positive electrode slurry on the aluminum foil, and place the aluminum foil in a vacuum oven at 80°C to dry for 20h to 24h, and then use a cutting machine to cut it into discs with a diameter of 12mm, and roll it under a pressure of 5MPa, and finally vacuum dry it at 80°C for 10h to 12h to obtain a lithium-ion battery positive electrode sheet, which is transferred to a glove box for storage. The other steps are the same as those in Specific Embodiments 1 to 9.

[0049] The following examples are used to verify the beneficial effects of the present invention:

[0050] Example 1: A method for preparing a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material, which is specifically completed by the following steps:

[0051] 1. Preparation of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium:

[0052] ①. At room temperature, add 20 mmol sodium hydrosulfide and 10 mmol lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide (LiCPSI) to 20 mL anhydrous methanol, and then heat to 65°C under nitrogen protection, and heat to reflux at 65°C for 24 hours. After the reaction is completed, filter to remove impurities, and perform rotary evaporation of the filtrate at 50°C for 0.5 hours. The product is a transparent oil, and the reaction product I is obtained;

[0053] The preparation method of lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide described in step 1① is specifically completed according to the following steps: dissolving 200mmol LiOH·H2O in 20mL C2H3N solution, and then adding 100mmol C3H6Cl2O2S and 100mmol CH2F3NO2S in an ice-water bath, stirring for 48h, and then filtering, and concentrating the filtrate at 50°C with a rotary evaporator to obtain a reaction product; dissolving the reaction product in 20mL dichloromethane, filtering again, and drying the filtrate at 50°C with a rotary evaporator to obtain lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide;

[0054] ②, add 50 mL of acetonitrile to the reaction product I, stir evenly and filter again, and perform rotary evaporation on the filtrate at 50° C. to obtain the reaction product II; place the reaction product II in an oven at 80° C. and dry for 12 h to obtain thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium (SH-LiCPSI);

[0055] 2. Preparation of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite:

[0056] ①. At room temperature, 3.5 mmol of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium (SH-LiCPSI), 1 mmol of tripropylene phosphite (TLP) and 3 mmol of azobisisobutyronitrile were added to 20 mL of anhydrous tetrahydrofuran, and then heated to 65°C under nitrogen protection, and heated under reflux at 65°C for 12 h. After the reaction was completed, the filtrate was rotary evaporated at 50°C for 0.5 h to obtain reaction product III;

[0057] ②. Add the reaction product III into 50 mL of dichloromethane, stir evenly and filter again, and rotary evaporate the filtrate at 50°C for 0.5 h to obtain the reaction product IV; dry the reaction product IV in an oven at 80°C for 12 h to obtain the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material (SH-LiCPSI-TLP).

[0058] Example 2: A lithium ion battery positive electrode material is coated with a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material prepared in Example 1, specifically according to the following steps:

[0059] 1. Thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material (SH-LiCPSI-TLP) and N-methylpyrrolidone (NMP) were fully stirred in a glove box (H2O<0.1ppm; O2<0.1ppm) to obtain a SH-LiCPSI-TLP / NMP mixed solution;

[0060] The mass fraction of the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material in the SH-LiCPSI-TLP / NMP mixed solution described in step 1 is 20%;

[0061] 2. Mix 20 mg SH-LiCPSI-TLP / NMP mixed solution, 2 g SC-NCM811 powder and 7 mL N-methylpyrrolidone (NMP), and then heat to 60 °C. Stir at 60 °C and 350 rmin. -1 The reaction was stirred for 12 h under the conditions of , and the N-methylpyrrolidone was completely volatilized to obtain a lithium-ion battery positive electrode material (M-TLP@SC-NCM811) coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite.

[0062] The SC-NCM811 powder described in Example 2 was purchased from Hefei Kejing Material Technology Co., Ltd., model: M2-S single crystal 811 lithium nickel cobalt manganese oxide.

[0063] The synthesis path of SH-LiCPSI-TLP is divided into two steps. The first step is the thiolation reaction of LiCPSI, and the second step is the thiol-ene reaction of SH-LiCPSI and TLP. The reaction process is as follows: Figure 1 As shown in a.

[0064] H NMR ( 1 H-NMR is an important characterization technique used to study molecular structure, configuration, conformation and molecular dynamics. 1 The structures of LiCPSI, SH-LiCPSI, TLP and SH-LiCPSI-TLP were analyzed by H-NMR, and the solvent was dimethyl sulfoxide (DMSO). Figure 1As shown in b and c. In addition to the internal reference peak, three groups of peaks were observed, and the area integration ratio between the three groups of peaks was 2:2:2, which is consistent with the expected molecular structure. Since the thiolation changes the functional group at the end of the LiCPSI carbon chain, the chemical environment of H on the carbon chain changes. Therefore, in the SH-LiCPSI spectrum, the chemical shifts of the three groups of peaks have changed. The area integration results and chemical position shifts are consistent with the molecular structure, indicating that the thiolation of LiCPSI is successful.

[0065] Figure 1 Where c is TLP and SH-LiCPSI-TLP 1 Comparison of H-NMR spectra. In the spectrum of TLP, three groups of peaks were observed in addition to the internal reference peak, and the area integration ratio between the three groups of peaks was 2:1:2, which was consistent with the expected molecular structure. In the spectrum of SH-LiCPSI-TLP, six groups of peaks were observed in addition to the internal reference peak, and the integrated area of ​​the six groups of peaks was 2, and the ratio between the peak areas was consistent with the structure. This shows that the thiol-ene reaction of SH-LiCPSI and TLP was successful.

[0066] X-ray diffraction (XRD) is a method to characterize the crystal structure and its changing rules. XRD was used to characterize the SC-NCM811 powder before and after coating. Figure 2 As shown. Comparing the angles of the diffraction peaks of SC-NCM811 before and after coating with the standard crystal card (ICSD#01-070-4314), it can be seen that there are no impurity peaks in the diffraction patterns before and after coating, indicating that the coating has not changed the crystal configuration of SC-NCM811. The separation degree between the two pairs of peaks (006) and (012) and (108) and (110) has not changed significantly, so the crystallinity of M-TLP@SC-NCM811 has not decreased due to the coating of SH-LiCPSI-TLP; in addition, the peak intensities of the (003) peak and the (104) peak have not changed significantly before and after coating, which shows that the degree of cation mixing in M-TLP@SC-NCM811 has not changed significantly.

[0067] In order to determine the changes on the single crystal surface before and after coating, scanning electron microscopy (SEM) tests were performed on the single crystal particles before and after coating. Figure 3 Figure a is a SEM image of a single Pristine SC-NCM811 particle. The single crystal particle is a polyhedral structure with a smooth surface and obvious edges and corners. There are only a few protrusions on the surface, which are presumed to be broken single crystal particles. Figure 3Figure b is a SEM image of a single M-TLP@SC-NCM811 particle. After being coated with SH-LiCPSI-TLP, the single crystal particle still maintains the basic polyhedral structure, but the surface is rough with moss-like protrusions, and obvious coating materials appear at the corners. It can be preliminarily concluded that SH-LiCPSI-TLP has been successfully coated on the surface of SC-NCM811.

[0068] Through SEM images, we can only observe the presence of SH-LiCPSI-TLP coating material on the surface of SC-NCM811, but we cannot determine whether SH-LiCPSI-TLP is evenly coated on the surface of SC-NCM811. Therefore, energy dispersive X-ray spectroscopy (EDS Mapping) is used to characterize the distribution of elements in M-TLP@SC-NCM811. Figure 4 From the dg graph, we can see that the distribution shapes of P, S, F, and N elements are almost consistent with the SEM shapes of M-TLP@SC-NCM811. Therefore, it can be determined that SH-LiCPSI-TLP has been uniformly coated on the crystal surface of SC-NCM811.

[0069] Application Example 1: The method for assembling M-TLP@SC-NCM811||Li is specifically completed according to the following steps:

[0070] 1. The lithium-ion battery cathode material (M-TLP@SC-NCM811) coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite, conductive carbon black (Super-P) and binder (polyvinylidene fluoride, PVDF) were mixed in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) was added and stirred at room temperature for 12 hours to obtain a cathode slurry;

[0071] The mass ratio of the total mass of the lithium ion battery positive electrode material coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite, the conductive carbon black and the binder to the N-methylpyrrolidone described in step 1 is 1:1;

[0072] 2. Use an automatic casting machine to evenly coat the positive electrode slurry on the aluminum foil, and place the aluminum foil in a vacuum oven at 80°C to dry for 24 hours, then use a cutting machine to cut it into discs with a diameter of 12 mm, and roll it under a pressure of 5 MPa for 10 seconds, and finally vacuum dry it at 80°C for 12 hours to obtain the positive electrode sheet of the lithium-ion battery, and transfer it to a glove box for storage;

[0073] 3. Assembled in a glove box (H2O <0.1ppm, O2 <0.1ppm), the battery composition is (from the negative electrode battery shell to the positive electrode battery shell): negative electrode battery shell, stainless steel spring, stainless steel gasket, lithium sheet (thickness 0.4mm, diameter 14mm), PP diaphragm (Code), lithium ion battery positive electrode sheet (diameter 12mm, total load is about 5mg), positive electrode battery shell; the electrolyte composition is 1MLiPF6 in ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) (1:1:1 by volume) with 5wt.%fluoroethylene carbonate (FEC), the total addition amount is 100μL, which is added to the lithium sheet and diaphragm in two equal amounts; the battery shell is purchased from Code, model 2032.

[0074] Comparative Application Example 1: The difference between this embodiment and Application Example 1 is that the lithium-ion battery positive electrode material (M-TLP@SC-NCM811) coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite is replaced with the original SC-NCM811 (Pristine SC-NCM811). The other steps and parameters are the same as those in Application Example 1.

[0075] The reversibility of the electrochemical reaction of M-TLP@SC-NCM811 was determined by cyclic voltammetry (CV). Cyclic voltammetry was performed on the batteries assembled in Application Example 1 and Comparative Application Example 1. Figure 5 As shown; Figure 5 Cyclic voltammetry curves from the first to the fifth cycle of PristineSC-NCM811 and M-TLP@SC-NCM811, where a is PristineSC-NCM811 and b is M-TLP@SC-NCM811;

[0076] By comparing the overlap of the two CV curves, it can be judged that there is no significant difference in the reversibility of Pristine SC-NCM811 and M-TLP@SC-NCM811. Since SH-LiCPSI-TLP and SC-NCM811 have essential differences in structure, lithium ion dynamics and other properties, the introduction of the SH-LiCPSI-TLP coating layer will inevitably cause an increase in the polarization voltage of M-TLP@SC-NCM811. By comparing the size of the redox peak voltage in the CV curve, it can be found that the polarization voltage of M-TLP@SC-NCM811 has a smaller increase, so it can be inferred that SH-LiCPSI-TLP has a good lithium ion transfer rate. This conclusion will be confirmed in the subsequent rate performance test.

[0077] The modification principle of Ni-rich NCM by surface coating modification is mainly to avoid direct contact between the positive electrode material and the electrolyte, thereby reducing the side reactions at the interface, extending the service life of Ni-rich NCM and improving its electrochemical performance. In order to broaden the use scenarios of Ni-rich NCM, the coating material is required to not only play a modification role under normal conditions, but also have a certain modification effect in some harsh environments (high temperature, high pressure, etc.). Therefore, in order to verify the improvement of the cycle performance of SC-NCM811 by SH-LiCPSI-TLP under various environments, the present invention designed cycle performance tests under three conditions, namely: room temperature standard voltage (25°C, 3.0V-4.3V), high temperature standard voltage (40°C, 3.0V-4.3V), room temperature high voltage (25°C, 3.0V-4.5V); the cycle performance is as follows Figure 6 .

[0078] Figure 6 In a, M-TLP@SC-NCM811||Li exhibits a higher initial discharge specific capacity (M-TLP@SC-NCM811||Li: 169.45 mAh g -1 , Pristine SC-NCM811||Li: 165.99mAh g -1 In terms of capacity retention, the capacity of Pristine SC-NCM811||Li decays rapidly after 350 cycles, while M-TLP@SC-NCM811 still has a high capacity retention rate (100 cycles: M-TLP@SC-NCM811 85.24%, Pristine SC-NCM811||Li 82.33%; 300 cycles: M-TLP@SC-NCM811 67.91%, Pristine SC-NCM811||Li 66.13%; 600 cycles: M-TLP@SC-NCM811 52.78%, Pristine SC-NCM811||Li 19.74%;).

[0079] Figure 6 In figure b, after 500 cycles at 40°C and 1C, the capacity retention rate of M-TLP@SC-NCM811||Li is 56.42%, while the capacity retention rate of Pristine SC-NCM811||Li is 49.26%. Therefore, it can be inferred that SH-LiCPSI-TLP has high thermal stability, which enables it to provide sufficient protection for SC-NCM811 in high temperature environments. Figure 6In Figure c, under high-voltage conditions, the capacity retention rate of M-TLP@SC-NCM811||Li is still 28.17% after 900 cycles, which is 3.62% higher than that of Pristine SC-NCM811||Li (24.55%).

[0080] In summary, SH-LiCPSI-TLP significantly improved the cycling performance of SC-NCM811 at room temperature and standard voltage. Even under high temperature / high pressure conditions, SH-LiCPSI-TLP can still play a certain modification role.

[0081] Since SH-LiCPSI-TLP contains lithium salt, it can theoretically improve the rate performance of SC-NCM811 to a certain extent when used as a coating material. Therefore, in order to verify the improvement of SC-NCM811 rate performance by SH-LiCPSI-TLP coating, the present invention conducted rate tests and constant current intermittent titration tests (GITT), such as Figure 7 .

[0082] Figure 7 In figure a, under low rate (C-rate < 0.3C), the discharge specific capacity of M-TLP@SC-NCM811||Li and PristineSC-NCM811||Li did not change significantly. However, when the rate increased, the discharge specific capacity of M-TLP@SC-NCM811||Li was significantly higher than that of PristineSC-NCM811||Li, and the difference between the discharge specific capacities increased with the increase of charge and discharge rate. At 5C rate, the discharge specific capacity of M-TLP@SC-NCM811||Li was 107.189.13mAhg -1 The specific capacity exceeds that of Pristine SC-NCM811||Li(98.05mAh g -1 ) about 9.13mAhg -1 . In addition, it is worth noting that at the 0.3C rate in the early stage of the cycle, there is no significant difference in capacity between Pristine SC-NCM811||Li and M-TLP@SC-NCM811||Li. However, after high-rate cycling, the capacity of Pristine SC-NCM811||Li is significantly lower than that of M-TLP@SC-NCM811||Li at the same rate (0.3C). It can be inferred that SH-LiCPSI-TLP can not only improve the rate performance of SC-NCM811, but also continuously protect SC-NCM811 at high current density.

[0083] Therefore, the present invention designs a cycle performance test at a large rate. Figure 7In Figure b, at a 3C charge and discharge rate, M-TLP@SC-NCM811||Li can maintain a high capacity retention rate and discharge specific capacity (50 cycles: M-TLP@SC-NCM811||Li 88.9%, Pristine SC-NCM811||Li 82.28%). Even at a 5C rate, although M-TLP@SC-NCM811||Li has a faster capacity decay, its capacity is still higher than that of Pristine SC-NCM811||Li. The reason for the increased capacity may come from the fact that the SH-LiCPSI-TLP coating layer increases the lithium ion dynamics in the electrode.

Claims

1. A method for preparing a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium: ①, at room temperature, sodium hydrosulfide and lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide are added to anhydrous methanol, and then heated under reflux for a period of time under nitrogen protection. After the reaction is completed, impurities are removed by filtration, and the filtrate is rotary evaporated to obtain reaction product I; ②, add acetonitrile to the reaction product I, stir evenly and filter again, and perform rotary evaporation on the filtrate to obtain the reaction product II; dry the reaction product II in an oven to obtain thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium; 2. Preparation of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite: ①, at room temperature, add thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium, tripropylene phosphite and azobisisobutyronitrile to anhydrous tetrahydrofuran, and then heat under reflux for a period of time under nitrogen protection. After the reaction is completed, the filtrate is rotary evaporated to obtain reaction product III; ②. Add the reaction product III into dichloromethane, stir evenly and filter again, and perform rotary evaporation on the filtrate to obtain the reaction product IV; dry the reaction product IV in an oven to obtain the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material.

2. The method for preparing a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material according to claim 1, characterized in that The preparation method of lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide described in step 1① is specifically completed according to the following steps: dissolving 200mmol LiOH·H2O in 20mL C2H3N solution, and then adding 100mmol C3H6Cl2O2S and 100mmol CH2F3NO2S in an ice-water bath, stirring for 48h, and then filtering, and concentrating the filtrate at 50°C with a rotary evaporator to obtain a reaction product; dissolving the reaction product in 20mL dichloromethane, filtering again, and drying the filtrate at 50°C with a rotary evaporator to obtain lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide.

3. The method for preparing a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material according to claim 1, characterized in that The molar ratio of sodium hydrosulfide to lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide described in step 1① is 2:1; the volume ratio of the amount of sodium hydrosulfide described in step 1① to anhydrous methanol is (15mmol-25mmol):(15mL-30mL); the heating reflux temperature described in step 1① is 65°C, and the heating reflux time is 20h-28h; the temperature of the rotary evaporation described in step 1① is 50°C-55°C.

4. The method for preparing a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material according to claim 1, characterized in that The volume ratio of the reaction product I described in step 1 ② to acetonitrile is 1 mL: (20 mL ~ 60 mL); the temperature of the rotary evaporation described in step 1 ② is 50 ° C ~ 55 ° C; the temperature of the drying described in step 1 ② is 70 ° C ~ 90 ° C, and the drying time is 10h ~ 14h.

5. The method for preparing a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material according to claim 1, characterized in that The molar ratio of the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium, tripropylene phosphite and azobisisobutyronitrile described in step 2① is (3mmol~4mmol):(0.5mmol~1.5mmol):(2.5mmol~3.5mmol); the volume ratio of the amount of thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium and anhydrous tetrahydrofuran described in step 2① is (3mmol~4mmol):(15mL~30mL); the heating reflux temperature described in step 2① is 65°C, and the heating reflux time is 10h~14h; the temperature of the rotary evaporation described in step 2① is 50°C~55°C.

6. The method for preparing a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material according to claim 1, characterized in that The temperature of the rotary evaporation in step 2② is 50°C; the temperature of the drying in step 2② is 70°C to 90°C, and the drying time is 10h to 14h.

7. Use of a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material prepared by the preparation method according to claim 1, characterized in that A thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material is used for coating anode materials of lithium ion batteries.

8. The use of a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material according to claim 7, characterized in that A thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material is used to coat a positive electrode material of a lithium ion battery, and is specifically completed by the following steps:

1. Thoroughly stir the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material and N-methylpyrrolidone in a glove box to obtain a SH-LiCPSI-TLP / NMP mixed solution; The mass fraction of the thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material in the SH-LiCPSI-TLP / NMP mixed solution described in step 1 is 15% to 25%; 2. Mix the SH-LiCPSI-TLP / NMP mixed solution, SC-NCM811 powder and N-methylpyrrolidone, then heat and stir for a period of time. After the reaction is completed, the N-methylpyrrolidone is completely volatilized to obtain a lithium-ion battery positive electrode material coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite.

9. The use of a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material according to claim 8, characterized in that The mass volume ratio of the SH-LiCPSI-TLP / NMP mixed solution, SC-NCM811 powder and N-methylpyrrolidone described in step 2 is (15mg-25mg):(1g-3g):(5mL-10mL); the temperature of the heating and stirring described in step 2 is 50°C-70°C, and the stirring speed is 350rmin -1 ~500rmin -1 The stirring time is 10h to 12h.

10. The use of a thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite organic coating material according to claim 8, characterized in that The method for preparing a positive electrode sheet of a lithium-ion battery using a lithium-ion battery positive electrode material coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite is specifically completed in the following steps:

1. The lithium-ion battery positive electrode material coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite, conductive carbon black and binder were mixed in a mass ratio of 8:1:1, and then N-methylpyrrolidone was added, and stirred at room temperature for 10h to 12h to obtain a positive electrode slurry; The mass ratio of the total mass of the lithium-ion battery positive electrode material coated with thiolated 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium-tripropylene phosphite, conductive carbon black and binder to N-methylpyrrolidone is 1:1; the binder described in step 1 is polyvinylidene fluoride; 2. Use an automatic casting machine to evenly coat the positive electrode slurry on the aluminum foil, and place the aluminum foil in a vacuum oven at 80°C to dry for 20h to 24h, then use a cutting machine to cut it into discs with a diameter of 12mm, and roll it under a pressure of 5MPa. Finally, vacuum dry it at 80°C for 10h to 12h to obtain the positive electrode sheet of the lithium-ion battery, and transfer it to a glove box for storage.

Citation Information

Patent Citations

  • Preparation method and application of organophosphate-coated high-nickel single-crystal ternary positive electrode material

    CN117913251A

  • Sodium-ion battery electrolyte capable of reducing gas production and battery manufacturing method

    CN118554005A